PADAT TEBAR OPTIMUM UNTUK MENDUKUNG OPTIMASI KUALITAS AIR DAN PRODUKSI TAMBAK INTENSIF UDANG VANAME (Litopenaeus vannamei) - Utami, Diah Ayu Satyari; Ramlanis, Afan Auriel; Faruq, Wifky Ezra Mohammad; Saputra, Fazril (JURNAL AKUAKULTURA, 2022)
This study aimed to determine the optimum stocking density that supported optimization of water quality and production of white shrimp (Litopenaeus vannamei) ponds. This study was conducted in 2 different cycles, namely cycles 14 and 15 and with different shrimp stocking densities in each cycle, namely 94 and 150 shrimp/m2. Each cycle and stocking density was represented by 2 ponds, namely ponds B5 and B6. Experimental animals used were white shrimp post-larvae stadia 9-10 (PL 9-10) with a size of 9-12 mm. Experimental parameters observed included water quality parameters (brightness, salinity, temperature, dissolved oxygen, pH, alkalinity, ammonium, and nitrite) and production performance (average body weight, average daily growth, biomass, feed conversion ratio, survival rate, and feed intake). Water quality of rearing medium reached the optimum value at a stocking density of 94 shrimp/m2. This was indicated by higher dissolved oxygen (4.0-5.3 mg/l) and lower ammonium (0.5-3.0 mg/l) compared to rearing ponds with a stocking density of 150 shrimp/m2 (4 0.0-5.0 mg/l; 1.0-3.0 mg/l). A stocking density of 94 shrimp/m2 showed a higher production performance than a stocking density of 150 shrimp/m2. This was indicated by the higher average body weight, average daily growth, and SR (18.20-19.77 g/shrimp; 0.30-0.48 g/day; 80.60-80.90%) and the lower FCR (1.11-1.33) at stocking density of 94 shrimp/m2 compared to 150 shrimp/m2 (17.18-17.40 g/shrimp; 0.45-0.50 g/day; 73, 92-78.32%; 1.64-1.75). The results of this study indicated that stocking density could affect water quality and shrimp production performance. The optimum shrimp stocking density in this study was 94 shrimp/m2.